An evaluation on the image of fast food restaurants using compromisedanalytical hierarchy process: A case of Labuan, Malaysia - Yeap, Siew Lin (2020)
Restaurant image can be defined as an immediate perception that arises in the mind of the customers when the name of the restaurant is mentioned. It is reported as an important construct that influences the customer purchase decision and loyalty. Therefore, evaluating and improving restaurant image should be seen as a continuous process. Otherwise, in a long-run, the restaurants, including the fast-food restaurants (FFRs), may lose their potential customers to the competitors. Unfortunately, the set of attributes proposed to evaluate the image of an FFR in every past study appears to be incomplete with the absence of a few crucial attributes. Besides, there is no study which has used the additional 3Ps (people, process, and physical evidence) marketing mix attributes to specifically understand the effect of these attributes on FFR image. In addition, the researchers are yet to propose a multi-attribute decision making (MADM)-based procedure to evaluate the image of FFRs; a procedure which can simultaneously (1) reveal the relative weights of restaurant image attributes and (2) rank the involved FFRs according to their overall image scores. Indeed, the information on the attribute weights helps to identify the proper strategies for improvement, whereas the ranking helps to identify the principal competitors in the marketplace. This research therefore aimed at introducing a MADM procedure to evaluate the image of four FFRs in Labuan, Malaysia namely McDonald's, MarryBrown, PizzaHut, and Kentucky Fried Chicken based on a comprehensive set of attributes. FFRs in Labuan were chosen for this research as it was discovered that there is still some room for improvement that can be considered by these FFRs to polish their image from the public’s perspective. In this research, firstly, an initial list of FFR image attributes was elicited from previous literature. This initial list was then further validated through a two-round Delphi survey involving a panel of ten experts. A questionnaire was then designed based on the finalized attributes, and the data collected from a sample of 251 respondents using the designed questionnaire were then processed using the compromised-analytical hierarchy process (C-AHP) technique. C-AHP was selected over the traditional AHP as it ensured the data for analysis were free from the issue of inconsistency. The C-AHP results suggest that the four FFRs should assign better attention on the following six most influential attributes if they wish to meaningfully improve their overall image from the public’s perspective: Hospitality, employees' problem-solving skill, employees' knowledge, food taste, physical cleanliness, and service response time. The FFR which tops the ranking was found to hold the highest performance scores with respect to these six attributes. Also, interestingly, the research reports employees' appearance and restaurant exterior as two least important image attributes. From the literature perspective, this research has contributed a proper FFR image evaluation procedure, which not only able to uncover the weights of image attributes but also ranks the FFRs involved in the investigation by computing their aggregated image scores. Meanwhile, from a practical perspective, the research has suggested some feasible strategies to improve the overall image of the involved FFRs.